If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 6z = 5z Solving 10 + 6z = 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 10 + 6z + -5z = 5z + -5z Combine like terms: 6z + -5z = 1z 10 + 1z = 5z + -5z Combine like terms: 5z + -5z = 0 10 + 1z = 0 Add '-10' to each side of the equation. 10 + -10 + 1z = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 1z = 0 + -10 1z = 0 + -10 Combine like terms: 0 + -10 = -10 1z = -10 Divide each side by '1'. z = -10 Simplifying z = -10
| 9p-10=10p | | 9-(5a+2)=-a+5 | | 8x^2-6x^2+7x=0 | | -6-3b=-4b | | 4cos^2x=5sinx-2 | | 9-4(4x-3)=3 | | 7x+5x=0 | | 4x^2+8x^2=0 | | 13+d-27=-3 | | 6(3x+6)=-3x-5(1+4x) | | 7/2=1/9x+26/9 | | 4x^2+3x^2-2x=0 | | 2=X+3x^2 | | -3(7n+4)=-2n+26 | | F(19)=4x+7 | | 256=(-4)x | | 0=-10k+5k | | x=-2+8 | | 5x+2(x+4)=5(2x+10) | | 3(-6-7b)=4(-5b-6) | | 11x+53=7x+55 | | -3-c-6=-3c-6 | | 0.02x-1=2.50 | | x+-10=2y | | -4(2x-3)=-4+6(x-4) | | 2(2r-1)=4r+10 | | 4v^5=4v^3 | | 25x-75=4x-4 | | -7(6x-5)=-42x-35 | | 7(12+x)=7x+84 | | 7(x+2)-2(2x+1)=27 | | 8x+100=9-5x |